Alternative Application of Oral History in the Secondary Classroom - Alan English (Educational Considerations, 2021)
While oral history has been demonstrated to hold potential as a more engaging and rigorous alternative to textbook-centered instruction, it has also failed to replace textbooks as the mainstream methodology in high school classrooms. Here, the author presents oral history data from Jim Walch, a WWII, Korean War, and Vietnam War veteran who “retired” as a Red Cross emergency relief worker as well as sample classroom activities derived from that data. The objective is that these sample activities may be received as more approachable than traditional oral history methodology to secondary teachers who are accustomed to textbook-based instruction. It is hoped that these approachable alternatives will encourage secondary teachers to adopt more engaging and rigorous methodologies such as oral history into their curriculum.
Keywords: oral history; engagement; rigor; WWII; Korean War; Vietnam War